Model-free kinetic analysis of thermal degradation of polystyrene and high-density polyethylene blends - Kasawat Tippaha (2018)
© 2016, Chiang Mai Journal of Science. All Rights Reserved. An objective of this work was to investigate kinetic information of a thermal degradation of polystyrene (PS) and high-density polyethylene (HDPE) blends under a pyrolysis atmosphere at different mixture compositions, using thermogravimetric analysis, operated non-isothermally, and model-free method. It was found that the degradation temperature range can be reduced by an addition of PS. This is probably due to an attack of PE by polystyryl radicals. With regard to an activation energy calculation based on model-free method, the activation energies of the thermal degradation tended to increase with a level of conversion, for all cases. The lower the level of conversion, the closer the activation energy value to that of 100%PS. With higher level of conversion, the activation energy values were approaching to that of 100% HDPE. This could be due to the fact that the polystyryl free radical from PS is diminished along the conversion path and, hence, at a higher level of conversion, the degradation process has no more influence of such free radical. Finally, the activation energy of single PS was lower than that of single HDPE and a proportion of PS to HDPE has no effect on the activation energy, but the level of conversion.